Solvent Effects on the Monomer/Hydrogen‐Bonded Dimer Equilibrium in Carboxylic Acids: (+)‐(S)‐Ketopinic Acid as a Case Study. Issue 12 (30th May 2016) - Rodríguez Ortega, Pilar Gema; Montejo Gámez, Manuel; Márquez López, Fernando; López González, Juan Jesús
Abstract: The hydrogen‐bond‐assisted self‐association process of a chiral semirigid carboxylic acid, namely, (+)‐( S )‐ketopinic acid, has been studied. The multiconformational monomer/dimer equilibrium has been evaluated by means of a concentration‐dependent FTIR study that enabled the experimental equilibrium constants of the dimer formation reaction ( K dim ) to be determined in two solvents of different polarity. In CDCl3, dimeric forms predominate, even in diluted solutions ( K d i m C F =5.074), whereas in CD3 CN the self‐association process is hindered and monomers are always the main species, irrespective of solute concentration ( K d i m A N =0.194). The reliability of the dimerization constants and the derived mono‐ and dimeric experimental fractions have been proven by means of accurate matching between the experimental vibrational circular dichroism spectra of the species and the theoretical spectra generated by considering the simultaneous weighted contributions of the concomitant monomers and dimers. Abstract : Structures of states : The experimental determination of dimerization constants of (+)‐( S )‐ketopinic acid and subsequent estimation of the fraction of concomitant mono‐ and dimeric forms as a function of concentration allow the vibrational circular dichroism spectra of the species in chloroform and acetonitrile to be reproduced theoretically (see figure).